2009
DOI: 10.1016/j.sbi.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Nuance in the double-helix and its role in protein–DNA recognition

Abstract: It has been known for some time that the double-helix is not a uniform structure but rather exhibits sequence-specific variations that, combined with base-specific intermolecular interactions, offer the possibility of numerous modes of protein-DNA recognition. All-atom simulations have revealed mechanistic insights into the structural and energetic basis of various recognition mechanisms for a number of protein-DNA complexes while coarser grained simulations have begun to provide an understanding of the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 58 publications
(28 reference statements)
1
112
0
2
Order By: Relevance
“…We assumed that the flexibility of DNA, which can have a major effect on the specific affinity of a protein for DNA, has a minor effect on nonspecific protein-DNA interactions. [82][83][84][85] The protein and the DNA were placed in a box with dimensions of 350 Å × 350 Å × 350 Å, with the DNA being placed at the center of the box along its z-axis.…”
Section: Simulation Modelmentioning
confidence: 99%
“…We assumed that the flexibility of DNA, which can have a major effect on the specific affinity of a protein for DNA, has a minor effect on nonspecific protein-DNA interactions. [82][83][84][85] The protein and the DNA were placed in a box with dimensions of 350 Å × 350 Å × 350 Å, with the DNA being placed at the center of the box along its z-axis.…”
Section: Simulation Modelmentioning
confidence: 99%
“…In biological complexes it was already verified that the substitution of one single amino acid in the protein domain involved in recognition could induce a change on the DNA sequence that is recognized (Khorasanizadeh, 2004;Rohs et al, 2009). Although the bases' exposure is an important factor to determine the interaction with proteins, these complexes are stabilized for additional contacts between the lateral chains of amino acids and the deoxyribose rings and phosphate groups.…”
Section: Cellular Protein-dna Complexesmentioning
confidence: 99%
“…The possibility of numerous modes of protein-DNA recognition is related with some particularities of the nucleic acid molecule, such as its flexible structure, the presence of sequence-specific variations, combined with base-specific intermolecular interactions (Rohs et al, 2009). Unfortunately, the dependence of structure on sequence is not so well determined, since certain nucleotide sequences do not produce well-defined NMR maps.…”
Section: Dna Double Helixmentioning
confidence: 99%
See 1 more Smart Citation
“…An explanation for these phenomena might be found in the 3D structure of DNA (20). We recently showed that DNA shape plays an important role in protein-DNA recognition (21)(22)(23)(24).…”
mentioning
confidence: 99%